2016
DOI: 10.1021/jacs.6b11683
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional (C4H9NH3)2PbBr4 Perovskite Crystals for High-Performance Photodetector

Abstract: Two-dimensional (2D) layered hybrid perovskites of (RNH)PbX (R is an alkyl and X is a halide) have been recently synthesized and exhibited rich optical properties including fluorescence and exciton effects. However, few studies on transport and optoelectronic measurements of individual 2D perovskite crystals have been reported, presumably owing to the instability issue during electronic device fabrications. Here we report the first photodetector based on individual 2D (CHNH)PbBr perovskite crystals, built with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
332
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(338 citation statements)
references
References 27 publications
5
332
1
Order By: Relevance
“…Special micromorphologies such as 2D nanoplates, 1D NWs, 0D nanocrystals, nanonets, and inverse opals‐type structures have been carefully studied and showed superior optical properties and excellent electrical characteristics 52, 53, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. These structures will be discussed in detail in the following sections.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…Special micromorphologies such as 2D nanoplates, 1D NWs, 0D nanocrystals, nanonets, and inverse opals‐type structures have been carefully studied and showed superior optical properties and excellent electrical characteristics 52, 53, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65. These structures will be discussed in detail in the following sections.…”
Section: Factors Influencing Photodetectors Performancesmentioning
confidence: 99%
“…Such an efficient photoresponse is most likely attributed to the strong adsorption of 2D perovskite crystals on and enhanced carrier collection by graphene electrodes. This report represents the first time to fabricate a novel photodetector based on 2D individual perovskite crystals combining graphenebased source-drain electrodes, and the results could open a new avenue for the development perovskite crystals based optoelectronic devices [58].…”
Section: Photodetectors Based On 2d Layered Perovskitesmentioning
confidence: 90%
“…Moreover, the geometrical distortion of perovskite layers can also affect the defectivity and charge relaxation dynamics. Tan et al reported the synthesis of (C 4 H 9 NH 3 ) 2 PbBr 4 crystals by a solution-processed method, which have a domain size of several to tens of micrometers and the thickness of several to tens of nanometers [58]. PbBr 6 octahedra are connected to each other via corner-sharing bromide atoms forming a 2D perovskite layer in the bc-plane, as shown in Figure 4a.…”
Section: General Structural Featuresmentioning
confidence: 99%
See 2 more Smart Citations